Impact of cavity and infiltration on pulmonary function and health-related quality of life in pulmonary Mycobacterium avium complex disease: A 3-dimensional computed tomographic analysis. (May 2017) - Asakura, Takanori; Yamada, Yoshitake; Namkoong, Ho; Suzuki, Shoji; Niijima, Yuki; Kamata, Hirofumi; Funatsu, Yohei; Yagi, Kazuma; Okamori, Satoshi; Sugiura, Hiroaki; Ishii, Makoto; Jinzaki, Masahiro; et al.
Abstract: Background and objectives: Pulmonary Mycobacterium avium complex (pMAC) disease manifests as various types of lesions, such as infiltrates, nodules, cavities, and bronchiectasis. However, the important determinants for clinical parameters in lung involvement are poorly understood. The objective of this study was to obtain quantitative parameters by 3-dimensional CT, and investigate the relationship between these parameters and the pulmonary function tests (PFTs) and health-related quality of life. Material and methods: Quantitative analysis using CT was performed in 67 pMAC patients. The relationship between new quantitative parameters for evaluating lung involvement using 3-dimensional CT and PFTs or St George's Respiratory Questionnaire (SGRQ) was evaluated. Results: The ratio of infiltration to total lung volume showed significant correlation with the PFT results, especially the percent-predicted forced vital capacity (%FVC; ρ = −0.52), residual volume (ρ = −0.51), and total lung capacity (ρ = −0.59). The cavity volume was strongly correlated with the %FVC (ρ = −0.78) in the cavity group, while the ratio of infiltration to total lung volume was strongly correlated with the %FVC (ρ = −0.53) in the non-cavity group. The ratio of infiltration to total lung volume was significantly correlated with all SGRQ parameters (ρ = 0.41–0.52) in the non-cavity group. Conclusions: Infiltration was an important parameter for the PFTs and SGRQ in pMAC patients according to the 3-dimensional CT analysis. Moreover, cavity volume was an important parameter of the PFTs in the cavity group. Therefore, infiltration and cavity volume are key features for the management of pMAC disease. Highlights: Development of a novel evaluation system using 3D-CT analysis for pMAC disease. Infiltration was an important parameter for the PFTs and SGRQ. The cavity volume was strongly correlated with the PFT results in the cavity group.